Theranostics in Pancreatic Neuroendocrine Neoplasms: From Molecular Imaging to Personalized Radionuclide Therapy - Takehiro Okabayashi; Ryo Inada; Motoyasu Tabuchi; Rika Yoshimatsu; Yuji Negoro; Akihito Nishioka (Radiation, 2026)
Pancreatic neuroendocrine neoplasms (PanNENs) are a heterogeneous group of tumors characterized by variable biological behavior and frequent overexpression of somatostatin receptors, making them ideal candidates for theranostic approaches. Over the past two decades, advances in molecular imaging and peptide receptor radionuclide therapy (PRRT) have fundamentally transformed the diagnosis and management of advanced PanNENs, establishing nuclear medicine as a central component of precision oncology. This review provides a comprehensive overview of the evolving role of theranostics in PanNENs, with particular emphasis on recent developments in nuclear medicine and radiation-based precision medicine. We discuss the biological foundation of molecular imaging, current clinical evidence supporting PRRT, and emerging strategies for personalized radionuclide therapy based on quantitative imaging, patient selection, and individualized dosimetry. Furthermore, we highlight next-generation radiopharmaceuticals, including somatostatin receptor antagonists and α-emitting radionuclides, as well as novel diagnostic tracers that are expanding the scope of theranostic applications. The review also examines the growing impact of artificial intelligence, radiomics, and computational modeling in image analysis, treatment planning, and adaptive radionuclide therapy. Finally, we discuss future perspectives toward adaptive precision theranostics, in which molecular imaging, multi-omics integration, advanced dosimetry, and artificial intelligence converge to support dynamic, patient-specific treatment strategies. Continued technological innovation and multidisciplinary collaboration are expected to further establish theranostics as a cornerstone of personalized management for patients with PanNENs.